IMPAIRMENT OF HERP E3 LIGASE ACTIVITY BY MUTANT POLYGLUTAMINE PROTEINS: A NOVEL MECHANISM IN POLYGLUTAMINE DISEASE NEUROPATHOLOGY (European Journal of Histochemistry)
Herp (Homocysteine-induced endoplasmic reticulum protein) is an endoplasmic reticulum stress (ERS) response protein that regulates the clearance of misfolded proteins via the ER-associated degradation (ERAD) pathway. This study demonstrates for the first time that Herp possesses E3 ubiquitin ligase activity, catalyzing polyubiquitination of mutant huntingtin (mHtt) through K48- and K63-linked chains, thereby suppressing its aggregation and promoting proteasome-dependent degradation. Additionally, the ubiquitin-like (UBL) domain of Herp independently inhibits the aggregation of various polyglutamine (polyQ) proteins, suggesting its broad-spectrum anti-polyQ toxicity function. However, in polyQ diseases, caspase-7-mediated cleavage of Herp results in the loss of 33 C-terminal amino acids (Herp△33), converting its catalytic property from polyubiquitination to monoubiquitination and forming non-canonical K33-linked ubiquitin chains. This shift markedly enhances the stability of polyQ proteins, facilitating their aberrant accumulation. Herp△33 itself autonomously forms insoluble aggregates, impairs the complete activation of endoplasmic reticulum-phagy (ER-phagy) pathway, and exhibits strong cytotoxicity. Herp△33 knock-in mice display progressive cognitive, memory, and motor coordination deficits, accompanied by Herp△33 aggregation and prominent neurodegenerative pathology in the striatum. This study reveals the critical role of Herp’s enzymatic switch and the aggregation toxicity of its cleavage product (Herp△33) in polyQ diseases, providing a crucial theoretical foundation for further investigation into Herp’s novel functions and the pathogenesis of polyQ disorders.